Anamnesis: Paul Celan's Translations of Poetry - Leonard Olschner (Studies in 20th & 21st Century Literature, 1988)
Paul Celan's significance as a poet has long been undisputed, and increasingly outside German-speaking countries, but his translations of poetry have remained at the periphery of critical attention and are only gradually becoming recognized as an integral and indeed major part of his poetry and poetics. The present essay attempts to elucidate specific aspects of the biographical, linguistic, literary and historical background at work in Celan's translating and offers analytic interpretations of texts by Mandel'stam, Apollinaire and Shakespeare in Celan's translation.
Keywords: Paul Celan; German; German-speaking; poetry; translation; poetics; biographical; linguistic; literary; historical background; Mandel' stam; Apollinaire; Shakespeare